2018
DOI: 10.1007/s11661-018-4752-7
|View full text |Cite
|
Sign up to set email alerts
|

On the Effect of Environmental Exposure on Dwell Fatigue Performance of a Fine-Grained Nickel-Based Superalloy

Abstract: The influence of sulfur contamination on the corrosion-fatigue behavior of a polycrystalline superalloy used in aero-engines is considered. Samples tested under a variety of environmental conditions (including exposures to air, SO x gas, and salt) are characterized through a suite of high-resolution characterization methods, including transmission electron microscopy (TEM), secondary ion mass spectroscopy (nanoSIMS), and atom probe tomography (APT). The primary effect of sulfur contamination is to accelerate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…Another similar experiment was performed on a Ni-Cr-Al based turbine disc alloy (RR1000) performed at 750⁰C in air +300 ppmv SO2/3 and NaCl-Na2SO4 salts (both under static furnace exposures and under dynamic fatigue testing conditions) and in the absence of Nb, Ti-rich Cr sulfides formed instead [48], [49]. It is possible that Nb suppresses the formation of Cr3S2 as well, though more studies will be required to prove this.…”
Section: The Reactions Explained Inmentioning
confidence: 98%
“…Another similar experiment was performed on a Ni-Cr-Al based turbine disc alloy (RR1000) performed at 750⁰C in air +300 ppmv SO2/3 and NaCl-Na2SO4 salts (both under static furnace exposures and under dynamic fatigue testing conditions) and in the absence of Nb, Ti-rich Cr sulfides formed instead [48], [49]. It is possible that Nb suppresses the formation of Cr3S2 as well, though more studies will be required to prove this.…”
Section: The Reactions Explained Inmentioning
confidence: 98%
“…A previous study employed advanced atom probe characterization techniques to identify sulphide reactions at subsidiary crack tips in specimens sourced from this same research project. 27 Notably, those samples related to identical corner cracks growing in a salt and SO 2 environment were characterized on a nearsurface plane. Irrespective of the precise crack tip damage mechanism, no significant effect on the rate of crack growth was reported because of the complex sulphidation reactions, and those findings are replicated by the current data.…”
Section: Discussionmentioning
confidence: 99%
“…It is impossible to conclude whether these sulphides formed concurrent with the crack advancing or developed behind the crack tip in the wake of cracking. A previous study employed advanced atom probe characterization techniques to identify sulphide reactions at subsidiary crack tips in specimens sourced from this same research project 27 . Notably, those samples related to identical corner cracks growing in a salt and SO 2 environment were characterized on a near‐surface plane.…”
Section: Discussionmentioning
confidence: 99%
“…73 Correlative SEM, controlled electron channeling contrast imaging (cECCI), and APT (Figure 5) has revealed a high density of Cr, Co decorated dislocations, enabling rapid Cr, Co transport through pipe diffusion, and γ′ precipitate dissolution due to local chemical inhomogeneities. The investigation of crack tips using correlative microscopy with APT enabled the identification of alumina and chromia oxide intrusions ahead of crack tips 74 as well as the identification of layered oxide scales within the cracks, 12,75 offering new insights into the failure mechanisms. Using SEM and NanoSIMS (Figure 6a-b), Viskari et al 75 found that oxygen enters intergranular cracks without penetrating into the GB ahead of the crack tip, nor into the adjacent grains, as was verified by APT.…”
Section: Contributions Of Atom Probe Tomography and Correlative Micro...mentioning
confidence: 99%
“…Through combination of APT with other investigation tools, a broad range of material properties can be characterized at varying length scales and with complementary precision, enabling further understanding of the mechanisms underpinning corrosion and stress-corrosion cracking. [11][12][13] This article discusses current scientific knowledge of nickelsuperalloys and the role of alloying additions on phase stability and corrosion resistance, with a particular emphasis on additions of W and Moknown for improving creep resistance. The use of correlative microscopy with atom probe tomography (APT) to understand key oxidation and corrosion mechanisms, including crack investigation is reviewed.…”
Section: Introductionmentioning
confidence: 99%